Africans in the Americas a history of the black diaspora - Conniff, Michael L. 1942-; Davis, Thomas J. (St. Martin's Press, 1994)
By offering a complete view of African-American history and by considering the roles of Africans and their descendants in the development of all the Americas, the book is able to place the black diaspora in the larger context of world history